Indigenous knowledge systems for land condition assessment and sustainable land management in the Talensi District, Ghana - Latif Iddrisu Nasare; Latifa Abdul Rahman; Francis Diawuo Darko (Brawijaya University, 2023)
The quest for sustainable land management has led to the development of modern technologies for land condition assessment and management, but these approaches have often failed in rural contexts due to their high complexity and incompatibility with the socio-economic conditions of land users. Although indigenous systems are known to be accessible, compatible, and economically affordable for rural farmers, less is known about indigenous technologies for the assessment of the land condition and sustainable land management. The present study identified indigenous indicators for the assessment of land degradation and examined indigenous practices for sustainable land management in the Talensi district of the Upper East region of Ghana. The study employed a qualitative approach in which interviews were conducted with sixty farmers in three selected communities of the Talensi district. Generally, land degradation was observed by respondents in the form of soil degradation or loss of vegetative cover. Among indigenous indicators of land degradation, soil erosion emerged as the most frequent indicator (75%), while the proliferation of mining pits (10%) was the least observed indicator. Indigenous practices for sustainable land management in the district include stone bunding, contour ploughing and zero tillage. The most used soil fertility improvement practice identified was crop rotation (47%) while the application of compost/manure occurred as the least (18%) practice. The study recommends that the Ministry of Food and Agriculture incorporate indigenous knowledge and technologies into land management programmes.